Modeling the Demand for Narrow Money in the United Kingdom and the United States. - Hendry, D; Ericsson, N (1991)
Despite the importance of well-specified empirical money-demand functions for inference, forecasting, and policy, problems in modeling have arisen concerning the economic theories of money demand, the data, institutional frameworks, financial innovation, and econometric implementation. By developing constant, data-coherent M1 demand equations for the United Kingdom and the United States, the authors investigate these issues and explain such puzzles as "missing money," the great velocity decline, and the recent explosion in M1. The endogeneity of money, the Lucas critique, and the non-invertibility of their M1 models are also discussed.